PORCINE CYSTICERCOSIS RISKS: AWARENESS, ATTITUDES AND PERCEPTIONS ON SAFETY PRACTICES AMONG FARMERS, BUTCHER-OWNERS AND CONSUMERS IN WESTERN KENYA PORCINE CYSTICERCOSIS RISKS: AWARENESS, ATTITUDES AND PERCEPTIONS ON SAFETY PRACTICES AMONG FARMERS, BUTCHER - Mwabonimana, Marie-Francoise; Macharia King’ori, Anthony; Muleke Inyagwa, Charles; Omedo Bebe, Bockline (African Journal of Infectious Diseases (AJID), 2020)
Background: The demand of pork has increased in the world with high need in animal protein in Africa. The pork safety and quality need to be improved up to reach the consumer trust and prevent them from Porcine Cysticercosis (PC) contamination. This study assessed the awareness, attitudes and safety practices for risk of PC among farmers, butcher-owners and consumers. Methodology: Data was obtained using structured questionnaire in a cross sectional survey interviews with 280 respondents composed of 162 farmers, 26 butcher-owners and 92 consumers from two Counties (Busia and Kakamega) in Western Kenya. The extent of awareness, attitudes and safety practices were estimated using Chi - square test. Results: Results reveal that a larger majority of farmers had low knowledge of pig management systems (82.7%), risks for PC transmission (78.4%) and Taenia solium parasite (75.9%). More of the butcher-owners associated high risk of PC infection with pork from slaughter slabs (69.3%) and from home slaughters (76.9%) but considered pork from eateries as safe (73.1%). For consumers, majority strongly agreed that pork sold (85.9%), from slaughter slabs (92.4%) and from butcheries (81.5%) are safe but pork from the eateries as less safe (64.1%). Conclusion: Results indicate low knowledge of management and risk factors for PC transmission at production level in the study area while butcher-owners and consumers hold different views about where safe pork is found in the market. Therefore, public education about PC risks and pork safety is necessary among all stakeholders in the pork value chain in Western Kenya.